Development of hydroxy-based sphingosine kinase inhibitors and anti-inflammation in dextran sodium sulfate induced colitis in mice. Issue 14 (15th July 2016) - Xi, Meiyang; Ge, Jun; Wang, Xiaojian; Sun, Chenbin; Liu, Tianqi; Fang, Liang; Xiao, Qiong; Yin, Dali
Graphical abstract: Highlights: We discovered the trihydroxybenzohydrazide scaffold as an SphK inhibitor. 51 derivatives were synthesized and evaluated for SAR study. The most potent compound33 decreased SphK expression in HCT116. 33 significantly inhibited DSS induced colitis in mice. 33 inhibited IL-6 and COX-2 overexpression induced by DSS. Abstract: Sphingosine kinase (SphK)-catalyzed production of sphingosine-1-phosphate (S1P) regulates cell growth, survival and proliferation as well as inflammatory status in animals. In recent study we reported the N ′-(3-(benzyloxy)benzylidene)-3, 4, 5-trihydroxybenzohydrazide scaffold as a potent SphK inhibitor. As a continuation of these efforts, 51 derivatives were synthesized and evaluated by SphK1/2 inhibitory activities for structure–activity relationship (SAR) study. Among them, 33 was identified as the most potent SphK inhibitor. Potency of33 was also observed to efficiently decrease SphK1/2 expression in human colorectal cancer cells (HCT116) and significantly inhibit dextran sodium sulfate (DSS)-induced colitis as well as the decreased expression of interleukin (IL)-6 and cyclooxygenase-2 (COX-2) in mouse models. Collectively, 33 was validated as an effective SphK inhibitor, which can be served as anti-inflammatory agent to probably treat inflammatory bowel diseases in human.